Impact of early statin therapy in patients with ischemic stroke or transient ischemic attack. (13th June 2013) - Chen, P.‐S.; Cheng, C.‐L.; Kao Yang, Y.‐H.; Yeh, P.‐S.; Li, Y.‐H.
<x xml:space="preserve">Abstract</x> Background Statin therapy has demonstrated benefits in ischemic stroke patients. However, little is known about whether the timing of statin initiation affects clinical outcomes. The possible association of statin use and cerebral hemorrhage is also a concern for early statin therapy after stroke. The objective of this study was to evaluate the efficacy and safety of the initiation timing of statins in acute ischemic stroke. Methods A cohort study was performed using 5‐year National Health Insurance Research Database in Taiwan. Patients without prior statin therapy admitted for their new ischemic stroke or transient ischemic attack (TIA) were enrolled. Patients were recognized as inhospital use group (2019 patients, statin initiation during hospitalization), intermediate use group (2266 patients, statin initiation within 1 year after discharge) or late use group (2958 patients, statin initiation 1 year later after discharge). The study endpoint was the composite outcome of ischemic stroke, TIA, hemorrhagic stroke, or acute coronary event. Results As compared with inhospital use, patients with late use had a 49% increased risk (adjusted HR: 1.49, 95% CI: 1.26–1.76) of composite endpoint. In contrast, patients with intermediate use had similar risk of endpoint as those with inhospital use. The risk of cerebral hemorrhage was similar in patients receiving inhospital, intermediate, or late statin treatment. Conclusions In acute ischemic stroke, patients receiving late statin treatment carried a poorer clinical outcome than those with earlier statin initiation. Inhospital statin use after an acute ischemic stroke did not increase the risk of cerebral hemorrhage.